Electrical current nanogeneration driven by spontaneous nanofluidic oscillations - Gimenez, Rocio Aldana (2018)
Exploiting natural phenomena is a central route for providing electricity to sustainably drive wearable electronics. Here we report a nano-scale water-driven energy generator that produces tiny electrical currents from spontaneous wetting-drying oscillations in mesoporous thin films. The system was fabricated with a wormlike mesoporous silica film, which was packed in between Cu and silicon contacts. The nanogenerator runs autonomously when a water droplet is laid over the film close to the Cu electrode, as water infiltration into the film under the electrode produces a direct-current. Wetting-drying cycles, which are spontaneously triggered by water evaporation, are perfectly correlated to the generated electrical current. The autonomous water displacement through the film yields a sustained energy conversion until the droplet reservoir vanishes. This novel water-driven nanogenerator opens new alternatives for versatile, mobile and cost-effective self-powering of nanosystems and nanodevices.